Antioxidant and ACE-Inhibitory Activity of Common Bean Whey Fortified Yoghurt with Assessed by in vitro Static Gastrointestinal Digestion - Ahmadullah Zahir; Zhuang Shen; Xin Rui; Jing Huang; Enayatullah Hamdard; Mingsheng Dong (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Yogurt supplemented with plant source proteins are received increased attention but few studies investigated effect of plant source proteins supplementation on protein digestibility and releasing of bioactive peptides. In this study, a residue rich in protein derived from common beans starch production, Common Bean Whey (CBW), was applied in development of novel yogurt. CBW from four major common beans varieties, namely white, black, kidney and cranberry were utilized. The novel yogurts were subjected to in vitro Gastro-Intestinal Simulation (GIS) digestion and protein digestibility, antioxidant activity and Angiotensin I Converting Enzyme (ACE) inhibitory property were studied. Compared to the control, Common Bean Whey Fortified Yogurt (CBWFY), particularly black bean whey was the predominate stable sample to protein degradation in the gastric and intestinal phases. Peptide content and SDS-PAGE revealed that CBWFY samples exhibited mostly lower hydrolysis grades in gastric and commence of duodenal phases. High antioxidant and ACE inhibitory activities results were attributed to CBWFY, in which significantly (p < 0.05) higher value was observed in kidney bean whey digesta at120min phase of intestinal digestion. For the first time, the outcomes of this investigation demonstrated the influence of four varieties of common beans whey supplementation on protein hydrolysis kinetics, digestive degree, antioxidant activity and ACE inhibitory properties on yogurt.